MATERNAL MORTALITY DUE TO PLACENTA ACCRETA AND ITS CAUSES (Journal of Medical & Health Sciences Review, 2025)
Background: Maternal death is also one of the significant issues in risky obstetrics, especially in low-resource tertiary care, where timely diagnosis and multidisciplinary integration might be constrained. The list of the most significant factors that contribute to maternal morbidity and mortality includes such problems as placenta accreta spectrum (PAS), since these conditions are linked to blood loss of monumental proportions, emergency interventions, and the occurrence of severe adverse perinatal complications. It involves the timely imaging, adequate preparation, and timely treatment of surgeries, yet death is predestined.Objective: To determine the mortality rate of the mother in relation to PAS and evaluate the clinical presentation, complications, and the outcomes of the treatment in the Jinnah Postgraduate Medical Centre, Karachi.Materials and Methods: The study was a cross-sectional study that was conducted during 12 Feb 2025 and 13 May 2025. This also involved pregnant women with PAS. Data were structured in proformas that were founded on the hospital abstractions, imaging reports, and operative notes. Maternal demographics, obstetric history, complications, interventions, and mortality outcomes were summarized with the aid of descriptive statistics.Results: 64 women at high-risk during obstetrics were recruited into the 3-month study period; 38 (59.4%) of them were PAS. Four patients died as a result of maternal mortality (6.3%). Placenta percreta was usually the cause of most of the complications related to PAS. The most prevalent in the PAS group consisted of postpartum bleeding (55%), the requirement for blood transfusion (52%), and emergency hysterectomy (29%). The commonest complications of preterm labor (46%). Massive hemorrhage (75%) and coagulopathy (25%) were the major causes of maternal mortality. Conclusion: PAS, especially the placenta percreta, is the most common cause of maternal mortality adds to maternal risk factors mainly by complicating preterm labor and leading to hemodynamic instability. To minimize deaths of mothers during high-risk pregnancy, early diagnosis, enhanced imaging, timely intervention, and multidisciplinary preparedness are vital. Enhancing risk-stratification and surgical preparedness can greatly enhance the outcomes.